Isolation of natural caffeine from liptonâ„¢ black tea through acid-base liquid-liquid extraction approach, its medical significance and its characterization by thin layer chromatography and IR analysis - Fazal-ur-Rehman, M.; Qayyum, Iqra; Manzar Zahra, Dr. (International Journal of Advanced Chemistry, 2021)
To isolate the caffeine from Liptonâ„¢ Black Tea Brand, a sequence of practices was applied. An Acid-Base Liquid-Liquid Extraction approach carried out to force the caffeine to be isolated in upper organic layer as extractant. By this method, first caffeine was isolated from tea bags through passing different steps of extraction, then caffeine was isolated from tea with the use of both Solid-Liquid approach as well as liquid-liquid extraction approach. A product of 0.05 g of pure caffeine was obtained giving the percentage yield or percent recovery of 1.22%. Calculated percent recovery was 1.2 %, this percentage yield clarified that in this tea brand, very small caffeine is investigated, this deduces a significant loss of product throughout the procedure which are due to formation of emulsions and not due to washing thoroughly with DCM to extract maximum yield. It is also significant to be considered that reactions of precursor with solvent pair may not be completed, so 100% yield is not conceivable. Due to much transfers in all processes, this loss might be occurred. Due to much transfers in all processes, this loss might be occurred thatâ€™s why repeated the process three times again. It is also revealed that as much water was added which decreased the concentration of Caffeine. On analysis with IR, Peak at f=3000Hz indicates the presence of -NH2 and -CONH2 groups while the peaks at f=1600 Hz and f=1750 Hz indicates the presence of alkene portion of the caffeine molecule which concluded that Caffeine is a purine base.Â Â